Instrumental Communication Actions By Investigators/Public Prosecutors As Objects of a State Administrative Lawsuit - Marbun, Rocky; Wijaya, Endra (KnE Social Sciences, 2022)
Law Number 8 of 1981 concerning the Criminal Procedure Code is legislation that has been positioned as a legal umbrella for every law enforcement officer. However, not all powers and discretion exercised by law enforcers—especially investigators and public prosecutors, can be tested or questioned for their validity through the submission of a pretrial application. One model of action that cannot be tested is the act of instrumental communication. Every act of instrumentalist communication always accompanies the application of the authority and discretion of the Investigator and Public Prosecutor, which causes harm to someone who is made a suspect and a defendant. This study aims to find opportunities for legal remedies that can be taken by suspects and defendants against acts of instrumental communication from law enforcement. This research is legal research using an interdisciplinary and multidisciplinary approach. The results of this study indicate that every act of instrumental communication that accompanies the use of authority and discretion and causes harm to the suspect and the defendant can be the object of a state administrative lawsuit based on Law Number 30 of 2014 concerning Government Administration. Keywords: criminal procedures, state administrative lawsuits, investigators, public prosecutors, communication actions